Socialization of Flood and Landslide Disaster Mitigation as a Lesson for Elementary School Students in Cikondang Village, Hantara District, Kuningan Regency - Yayan Suryana; Toto Supartono; Nunu Nugraha; Erlan Darmawan; Harun Al-Rasyid (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The geographical location of the Indonesian archipelago, which is at the meeting point of the Indo-Australian Plate, the Eurasian Plate, and the Pacific Plate, as well as the many mountains, valleys, and rivers, has caused Indonesia to frequently experience various disasters including earthquakes, landslides, floods, droughts, tsunamis, and others. The community's ignorance in dealing with various disasters has caused many victims which could have been reduced or avoided if they were willing to study the character of each disaster by carrying out disaster mitigation activities. Cikondang Village, Hantara District, Kuningan Regency is a village that has various unique features with varied land contours, there are low and highlands which have caused Cikondang Village to have various disaster risks because of its location on the Cipedak and Cibasale river flow routes, and also Mount Chulamega. , hills and valleys are also found around Cikondang. Among the most frequent threats are flash floods and landslides from cliffs in Cikondang Village. With disaster mitigation activities, it is hoped that the public will become aware of the importance of prevention through various efforts such as socializing natural disaster management and how to avoid them. Increasing knowledge of how to save oneself from various disasters is our goal in holding this disaster mitigation activity.